2014
DOI: 10.1016/j.aat.2014.09.003
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of surgical outcomes in patients aged 80 years and older

Abstract: Patients over the age of 80 years, of male sex, under general anesthesia, and receiving colloid infusion were at a higher risk of developing respiratory complications. Postoperative respiratory complications occurred in most of the geriatric surgical patients. Efforts to improve the surgical outcomes must include measures to minimize in-hospital complications. Detailed evaluation and better communicating the aforementioned risk factors to these patients are suggested for improving anesthesia quality and surgic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
2
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 22 publications
2
32
2
2
Order By: Relevance
“…Many of the studies showed the most common comorbidity was hypertension in elderly population, and diabetes mellitus and coronary artery disease were followed [2,10,11]. Contrary to Richmond et al [8], who reported the patients aged 85 years and older have lower mortality risk than the patients aged between 65 and 84 years, many studies have found an association between high age and mortality [6,9,13-16].…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Many of the studies showed the most common comorbidity was hypertension in elderly population, and diabetes mellitus and coronary artery disease were followed [2,10,11]. Contrary to Richmond et al [8], who reported the patients aged 85 years and older have lower mortality risk than the patients aged between 65 and 84 years, many studies have found an association between high age and mortality [6,9,13-16].…”
Section: Discussionmentioning
confidence: 91%
“…Orthopedic surgical procedures, especially for hip fractures, were commonly encountered in patients aged 80 years and older [1][2][3][4]. Because of the decreased cardiopulmonary capacity and multiple coexisting diseases, octogenarians and older have increased the risk of perioperative morbidity and mortality for hip fracture surgery [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Chung et al (19) reviewed 404 elderly cases who underwent surgery under the general anesthesia and evaluated post-operative complications. They found that 26.4% of patients developed one or more postoperative complications, and the in-hospital mortality rate was 6.7%.…”
Section: Discussionmentioning
confidence: 99%
“…Older patients with pre‐existing co‐morbidities have an increased risk of cardiovascular and cerebrovascular complications, resulting in prolonged hospitalization, intensive care unit (ICU) admission, increased morbidity and mortality, and healthcare expenditure …”
Section: Introductionmentioning
confidence: 99%
“…Age appears to be an important predictor of post‐operative outcome . Patients over the age of 70 years have higher post‐operative complications rates, which increase with each decade of life .…”
Section: Introductionmentioning
confidence: 99%